2020
DOI: 10.1111/jan.14670
|View full text |Cite
|
Sign up to set email alerts
|

Perceived participation and autonomy post‐stroke and associated factors: An explorative cross‐sectional study

Abstract: Aims To explore the level and associated factors of perceived participation and autonomy among stroke survivors in Shanghai, China. Design Cross‐sectional explorative study. Methods From January to December 2018, 431 patients presenting at the neurology departments of three hospitals with a confirmed diagnosis of stroke were recruited. Impact on Participation and Autonomy Questionnaire, modified Rankin Scale, Self‐efficacy for Managing Chronic Disease six‐item Scale, Medical Coping Modes Questionnaire and Mult… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
19
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(24 citation statements)
references
References 41 publications
4
19
1
Order By: Relevance
“…On the other hand, because of stigma, patients are reluctant to participate socially, which may incur discrimination. 8 The level of social participation in our study was much lower than that in Li et al’s study 35 with patients over three months poststroke and Chen et al’s study 36 with patients six months poststroke. It can be concluded that social participation levels are different in different phases of stroke survival.…”
Section: Discussioncontrasting
confidence: 72%
See 2 more Smart Citations
“…On the other hand, because of stigma, patients are reluctant to participate socially, which may incur discrimination. 8 The level of social participation in our study was much lower than that in Li et al’s study 35 with patients over three months poststroke and Chen et al’s study 36 with patients six months poststroke. It can be concluded that social participation levels are different in different phases of stroke survival.…”
Section: Discussioncontrasting
confidence: 72%
“…A much lower level of each domain of social participation among patients with stroke sequelae was found in this study than in other studies that investigated the social participation of common stroke survivors. 3,35,36 Therefore, researchers should pay much more attention to the study of different domains of social participation in the future.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The total score ranged from 12 to 84 with higher indicating higher level of social support. The Chinese version of MSPSS exhibited good reliability and validity ( Li et al., 2020 , 2021b ; Yang et al., 2020 ). In this survey, Cronbach's α coefficient of internal consistency of this scale was 0.949.…”
Section: Methodsmentioning
confidence: 98%
“…A prospective study of 52 stroke survivors further reported the role of balance self-efficacy and fall self-efficacy in predicting community reintegration [ 23 ]. A Chinese study also indicated that aside from physical function, self-efficacy was correlated most strongly with participation [ 24 ].…”
Section: Introductionmentioning
confidence: 99%